Exploring the Responsibilities of Wildlife Law Enforcement Officers: An Examination of Citations Issued by Kentucky Conservation Officers - Lanham, Conrad Morgan (2014)
Conservation officers are law enforcement agents whose primary responsibility is the enforcement of statutes regarding wildlife. Several bodies of research have noted the expansion of law enforcement capabilities and responsibilities of conservation officers to include the enforcement of general laws that fall outside the conservation officers' original mandate. The purpose of this study is to explore the work roles of contemporary conservation officers in Kentucky. Using data from citations issued by Kentucky conservation officers from 2006 to 2011, this research examines patterns of wildlife violations, boating violations, and general violations across time and space. Comparisons of these types of violations will describe how conservation officers spend some of their time and will assist the agency in determining if past and current directives have impacted enforcement priorities of officers. This scholarship introduces the theoretical framework of bureaucratization and growth complex as a tool to view changes in official mandates and job duties of Kentucky conservation officers and any changes in quantity and types of citations issued